Do Observed Teaching Behaviors Relate to Students’ Engagement in Physical Education? - González-Peño, Alba (Int J Environ Res Public Health, 2021)
Teachers’ behaviors can affect students’ engagement in the Physical Education (PE) setting. According to self-determination theory, teachers can rely on either a need-supportive or a controlling teaching behavior, and these behaviors will differently affect students’ outcomes. The main objective of this research was to analyse how teaching behaviors and some contextual variables influence students’ engagement in PE classes. The present study adds to the existing literature through an observation-based design in which real-life examples of need-supportive and thwarting teaching behaviors, as well as students’ engagement behaviors, have been identified. Thirty-seven different PE lessons were coded for 5-min intervals to assess the occurrence of 36 teaching behaviors and five students’ behaviors. Stepwise regression revealed that both structure during activity and relatedness support could predict student engagement in a positive way. Surprisingly, cold teaching also emerged as a direct predictor in the last step of the analysis. On the other hand, controlling and structure before activity behaviors inversely predicted students’ engagement. These four variables explained 39% of the variance in student engagement, whereas autonomy support did not correlate with student engagement. These new findings in the field not only confirm the known relevance of teaching behavior for students’ outcomes but also suggest an unexpected lack of influence of autonomy support on students’ engagement as well as an association between cold teaching and students’ engagement. Results are discussed in the light of new approaches, and some practical implications are provided.